Synthesis, Molecular Modelling and Antibacterial Activity Against Helicobacter pylori of Novel Diflunisal Derivatives as Urease Enzyme Inhibitors - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2019)
Background: The main factor for the prolongation of the ulcer treatment in the gastrointestinal system would be Helicobacter pylori infection, which can possibly lead to gastrointestinal cancer. Triple therapy is the treatment of choice by today's standards. However, observed resistance among the bacterial strains can make the situation even worse. Therefore, there is a need to discover new targeted antibacterial therapy in order to make success in the eradication of H. pylori infections. Methods: The targeted therapy rule is to identify the related macromolecules that are responsible for the survival of the bacteria. Thus, 2-[(2',4'-difluoro-4-hydroxybiphenyl-3-yl)carbonyl]-N-( substituted)hydrazinocarbothioamide (3-13) and 5-(2',4'-difluoro-4-hydroxybiphenyl-3-yl)-4-( substituted)-2,4-dihydro-3H-1,2,4-triazole-3-thiones (14-17) were synthesized and evaluated for antibacterial activity in vitro against H. pylori. Results: All of the tested compounds showed remarkable antibacterial activity compared to the standard drugs (Ornidazole, Metronidazole, Nitrimidazin and Clarithromycin). Compounds 4 and 13 showed activity as 2 mu g/ml MIC value. Conclusion: In addition, we have investigated binding modes and energy of the compounds 4 and 13 on urease enzyme active by using the molecular docking tools.
Keywords: Diflunisal; Helicobacter pylori; molecular docking; thiosemicarbazide; 1,2,4-triazole-3-thiones; macromolecules; HYDRAZIDE